2006
DOI: 10.1103/physrevlett.96.204302
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of Two-Dimensional Clusters of Rigid Rods in Air

Abstract: The scattering of sound waves by circular-shaped clusters consisting of two-dimensional distributions of rigid cylinders in air is studied in the low-frequency limit (homogenization) both theoretically and experimentally. Analytical formulas for the effective density and sound speed are obtained in the framework of multiple scattering. Here, an experimental demonstration is reported in which a cluster of wooden rods acoustically behaves as a cylinder of argon gas. Moreover, evidence is presented indicating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
77
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(79 citation statements)
references
References 15 publications
1
77
0
1
Order By: Relevance
“…A lattice of solid rods in air is an example of a two-dimensional (2D) sonic crystal (SC) that has been extensively studied since the nineties. [1][2][3][4] Most of the reported SCs were made of building units with negligible dissipation losses. However, in the last years, 2D SCs consisting of cylinders fabricated with lossy materials are deserving attention due to their potential application as acoustic barrier for broadband noise.…”
mentioning
confidence: 99%
“…A lattice of solid rods in air is an example of a two-dimensional (2D) sonic crystal (SC) that has been extensively studied since the nineties. [1][2][3][4] Most of the reported SCs were made of building units with negligible dissipation losses. However, in the last years, 2D SCs consisting of cylinders fabricated with lossy materials are deserving attention due to their potential application as acoustic barrier for broadband noise.…”
mentioning
confidence: 99%
“…It has been demonstrated that the homogenization of a SC takes place for wavelengths larger than a certain cutoff given approximately by c Ϸ 4a. 3 Since our fabricated GRIN lenses are based on hexagonal lattices with a = 2 cm, their focusing properties will appear at wavelengths Ն 8 cm, which corresponds to linear frequencies Յ 4.3 kHz. However, let us stress that the onset for the homogenization is not an exact parameter and we report below GRIN lenses working at 4.5 kHz, which is a frequency slightly above the cutoff c = 4.3 kHz.…”
mentioning
confidence: 99%
“…1 However, in the range of low frequencies ͑homogenization limit͒ they behave like homogeneous media whose effective acoustic parameters, dynamical mass density, and bulk modulus, basically depend on the lattice filling fraction. [2][3][4] The homogenization properties of SCs have been employed to design refractive devices like, for example, acoustic lenses whose focusing properties are based on their external curved surfaces [5][6][7] or Fabry-Perot type acoustic interferometers. 8 Gradient index ͑GRIN͒ sonic lenses based on homogenized 2D SCs have been proposed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated theoretically and experimentally that PCs with liquid crystal infiltration exhibit tunability on applying an external electric field [15]or changing the temperature [16][17][18][19][20]. If the constituent materials of PCs have magnetic permeabilities dependent on the external magnetic field, the photonic band gaps [PBGs] can be altered by changing the external magnetic field [21][22][23][24][25][26][27][28]. An electric or magnetic field changes the PBGs easily than the temperature.…”
Section: Introductionmentioning
confidence: 99%